Valley of refuge : a novel - Teschner, John (A Forge Book, published by Tom Doherty Associates/Tor Publishing Group, 2023)
"What would you do if you . . .were offered an obscene amount of money for your family's ancestral land? For Nalani and her mother, the money that could change their lives--at the sacrifice of everything they believe--is a double edged blade, and they're not sure they can trust the secretive tech billionaire holding it out to them as if it were an olive branch. But what happens when a man with unlimited wealth is given an answer he doesn't want to hear? What would you do if you . . .woke up on a plane en route to a tiny Hawaiian island, with no memory of who you are or why you're there? Janice, whose only clues are the passport in her pocket, and a locked phone with increasingly alarming text alerts about a situation she may or may not be part of, barely knows where to start. Navigating an unfamiliar place, and her own unfamiliar mind, Janice seeks to discover who she is, and answer the question of why she is here, and exactly whose side is she on? As plans are set in motion that carry them down dangerous and unexpected paths, all involved must decide just how far they are willing to go to reach their goals, before turning back is no longer an option."--